The Twits - Dahl, Roald; Blake, Quentin (London : Puffin Books, 2014)
Two terrible old people who enjoy playing nasty tricks are finally outwitted by a family of monkeys.
4.8
3-6.
3-6
Keywords: Monkeys -- Juvenile fiction; Practical jokes -- Juvenile fiction; Humorous stories; Monkeys -- Fiction; Practical jokes -- Fiction; Humorous fiction; Monkeys -- Fiction; Practical jokes -- Fiction; Humorous fiction